Adaptação transcultural de uma cartilha educativa para a prevenção da violência sexual na escola para a realidade da Costa Rica - Rivera, Alejandra Isabel Vargas (2017)
Adolescence is the transitional period from infancy to adulthood, characterized by social, emotional, mental, physical, and psychological changes. Sexual violence is one categorical type of violence that fundamentally affects this population, provoking serious health consequences. Confronting this reality, educational materials and protocols were developed, at an international level, but rarely reached intended youth groups. Therefore, the objective of this study is to carry out a cross-cultural adaptation of the “Sexual Violence Prevention in Schools” Educational booklet for Costa Rican youth reality. The methodological process followed Beaton et al (2007) “Cross-cultural Translation and Adaptation” protocol outlined by five steps: (1) the initial translation; (2) a synthesis of the preliminary translations; (3) a back-translation to the original language; (4) approval and review by panel of experts; and (5) a pre-test of the approved pre-final version. Study participants included two Costa Rican and two Brazilian translators, one Spanish linguistic professional, and one Brazilian Portuguese linguistic professional, seven experts of diverse professional backgrounds, and 61 adolescents between the ages of 10-13. Implemented data collection tools were: (1) “Validation Instrument of Semantic, Idiomatic, Cultural and Conceptual Equivalence” and “Content and Appearance Validation Instrument of the Educational booklet” adapted from previous studies. The sample size was through convenience, snowball effect, and protocol recommendation. Data collection occurred in the Republic of Costa Rica from April through September of 2017. National and international ethical aspects were obeyed, under the ethic committees of Costa Rica and Brazil. Data was presented with a scene imagery, absolute and relative frequency tables, tables with translated versions, syntheses and final versions of the educational booklet. The results were: (1) inconsistency related to the personal pronoun use in Spanish (vos, tu, and usted); (2) lack of inclusive language; (3) language and vocabulary not utilized by the target population; and (4) thematic and visual discrepancies due to contextual and cultural variance in Costa Rica. The decision was “needs reform”. In conclusion, the educational booklet is adapted culturally to the Costa Rican context, although require some reforms to fully fit the age group of the target population, also these studies are complex due to the adequacy of the images to a specific reality. This study recommends to evaluate the educational booklet with a larger sample and an age group of older adolescents.